Устойчивость растений к техногенным загрязнителям окружающей среды - Коршиков, И.И. (Промышленная ботаника, 2004)
The mechanisms of plants resistance to technogenous environmental pollutants are investigated on subcellular, organismic and populational levels. The results of long-term researches are generalized on the following aspects: phytotoxicity of separate xenobiotica and heavy metals; physical and biochemical changes in the leaves of arboreal plants growing on industrial sites of different manufactories of Donbass and also in the territory of a large industrial ity; adaptive changes of arboreal plants in the course of ontogenesis under extreme conditions of techogenically polluted territories; peculiarities of the structure of herbaceous plants populations colonizing mine-ore dumps; resistance to toxic gases and heavy metals of herbaceous plants seed progeny spontaneously invading technogenic ecotopes; the degree of aerotechnogenic emissions influence on conifers seminification; changies in genetic structures of mature plants and seed progeny of conifers populations damaged by emissional impact; selectional principles of resistance increase of arboreal plants used for optimization of techogenically polluted territories in steppe zone of Ukraine.